CRITICAL THINKING PROFILE OF MATHEMATICS IN INTEGRAL MATERIALS - Usman Aripin; Wahyu Setiawan; Heris Hendriana (Journal Of Educational Experts (JEE), 2019)
This study aims to determine the critical thinking skills of mathematics in one of the high schools in the city of Cimahi with indicators of mathematical critical thinking skills used are Analyzing and evaluating arguments and evidence, Arranging clarification, Arranging explanations based on relevant and irrelevant data, Identifying and evaluating assumptions . The method of this research is qualitative with descriptive research types. The research subjects were 76 students in one city of Cimahi. The data collection technique used in this study was a test of four items. Data analysis was carried out with 3 steps, namely data reduction, data presentation and conclusion drawing. The results showed that the average achievement test of students' mathematical critical thinking skills as a whole is still relatively low in the percentage of each indicator, 34% for indicators compose clarification, 5% analyze and evaluate arguments and evidence, 10% Prepare explanations based on relevant data and those that do not relevant and 64% Identifying and evaluating assumptions